2008
DOI: 10.1007/s11095-008-9539-x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose- and Metabolically Regulated Hepatic Insulin Gene Therapy for Diabetes

Abstract: Glucose- and metabolically controlled hepatic insulin gene therapy was obtained both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…However, their AAV production protocol utilizing helper adenovirus and observations that transgene expression was detected rapidly (within 24 h of viral injection) combine to suggest the presence of remnant helper adenovirus in their vector preparations [24]. Other studies have obtained hepatic transgenic insulin expression sufficient to partially ameliorate STZ-induced hyperglycemia in mice for up to 104 days by co-precipitating AAV with CaPO 4 or complexing with polyethylenimine before injecting directly into liver [25][26][27]. Yang et al [25] also used helper adenovirus to produce their AAV vectors, again suggesting additional effects to AAV2 transduction alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, their AAV production protocol utilizing helper adenovirus and observations that transgene expression was detected rapidly (within 24 h of viral injection) combine to suggest the presence of remnant helper adenovirus in their vector preparations [24]. Other studies have obtained hepatic transgenic insulin expression sufficient to partially ameliorate STZ-induced hyperglycemia in mice for up to 104 days by co-precipitating AAV with CaPO 4 or complexing with polyethylenimine before injecting directly into liver [25][26][27]. Yang et al [25] also used helper adenovirus to produce their AAV vectors, again suggesting additional effects to AAV2 transduction alone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts to mimic pancreatic function in regulating insulin have used nonislet cells, including hepatocytes, to express and secrete insulin (Lu et al 1998, Chen et al 2005, Wilson et al 2005, Hsu et al 2008. The general approach involved use of a glucose-responsive promoter or motif to control insulin gene transcription , Chen et al 2001, Alam & Sollinger 2002, Hsu et al 2008). An inherent feature of glucose-regulated insulin expression, as a control point, is that it gives rise to a lag phase during which the gene is transcribed and then translated.…”
Section: Discussionmentioning
confidence: 99%
“…This issue has been addressed using islet and non-islet cells (Efrat 1998, Yoon & Jun 2002, Olson & Thule 2008. In non-islet cell studies, proof of concept studies, in animals, using gene transfer to produce insulin involves a glucose-sensitive promoter that controls insulin gene transcription and thus in turn the synthesis of the hormone but not its secretion , Chen et al 2001, Alam & Sollinger 2002, Hsu et al 2008. In the absence of glucose-regulated insulin release, transcriptional control by itself might produce a lag phase in the secretory response of insulin to meals, which may lead to initial hyperglycemia followed later by hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…However, abnormal glucose tolerance was observed as a result of a lack of pancreatic transdifferentiation and expression of β-cell transcription factors. [105][106][107][108] Studies in our laboratory have also shown that these insulin-secreting liver cells are resistant to the detrimental effects of β-cell cytotoxins and proinflammatory cytokines that play a principle role in the pathogenesis of T1D. 109,110 In other experiments, no infiltrates of immune cells were observed in NOD mice engineered to express insulin in their livers.…”
Section: -101mentioning
confidence: 94%